Efflux pump inhibitors (EPIs) as new antimicrobial agents against Pseudomonas aeruginosa - Momen Askoura; Walid Mattawa; Turki Abujamel; Ibrahim Taher (Libyan Journal of Medicine, 2011)
Pseudomonas aeruginosa is an opportunistic human pathogen and one of the leading causes of nosocomial infections worldwide. The difficulty in treatment of pseudomonas infections arises from being multidrug resistant (MDR) and exhibits resistance to most antimicrobial agents due to the expression of different mechanisms overcoming their effects. Of these resistance mechanisms, the active efflux pumps in Pseudomonas aeruginosa that belong to the resistance nodulation division (RND) plays a very important role in extruding the antibiotics outside the bacterial cells providing a protective means against their antibacterial activity. Beside its role against the antimicrobial agents, these pumps can extrude biocides, detergents, and other metabolic inhibitors. It is clear that efflux pumps can be targets for new antimicrobial agents. Peptidomimetic compounds such as phenylalanine arginyl β-naphthylamide (PAβN) have been introduced as efflux pump inhibitors (EPIs); their mechanism of action is through competitive inhibition with antibiotics on the efflux pump resulting in increased intracellular concentration of antibiotic, hence, restoring its antibacterial activity. The advantage of EPIs is the difficulty to develop bacterial resistance against them, but the disadvantage is their toxic property hindering their clinical application. The structure activity relationship of these compounds showed other derivatives from PAβN that are higher in their activity with higher solubility in biological fluids and decreased toxicity level. This raises further questions on how can we compact Pseudomonas infections. Of particular importance, the recent resurgence in the use of older antibiotics such as polymyxins and probably applying stricter control measures in order to prevent their spread in clinical sittings.